Hispanocaderidae n. fam. (Hemiptera: Heteroptera: Tingoidea), one of the oldest lace bugs from the Lower Cretaceous Álava amber (Spain) - Golub, V. B.; Popov, Yu. A.; Arillo, A. (Zootaxa, 2012)
In this article described is a new monotypic fossil family Hispanocaderidae n. fam. (Hemiptera: Heteroptera) from theLower Cretaceous amber of Álava (Spain) clearly belonging to superfamily Tingoidea and at the same time possessing acomplex of distinctive features from other families of this superfamily, mostly of a plesiomorphic character. The complexof unique features of the new family includes: the longest antennal segment II, the presence of ocelli, very large ventrallyfaceted eyes, connection of peritreme of scent-ostiolar opening with base of costal area of hemelytron by groove asrudimentary state of ostiolar-stenocostal system but without stenocostal area, not fused hemelytral veins R+M and CuA,very broad abdominal laterotergits separated from mediotergites by sutures dorsally and ventrally. The described taxon probably represents one of the ancestral forms of the Cantacaderinae Stål (Tingidae) or Cantacaderidae sensu Lis.